Quantum computing using photons - Couteau, Christophe (The European physical journal. A, Hadrons and nuclei, 2025)
Photons as quantum bits have been amongst the first physical systems to be used for experimentally demonstrating some of the basic concepts in quantum computing starting from entanglement, to teleportation, to the realisation of a two-qubit CNOT gate and more recently for demonstrating quantum advantage using light. Photons can thus be used as qubits and are a potential platform for a future quantum computer. It is hard to predict which platform will win the race, perhaps none of them will surpass the others. What is for sure is that light can not be ignored altogether as this is the building block for communications and for propagating information in general, and thus for quantum information, in particular over long distances through optical fibres or via satellites. We will first develop what are the different ways of encoding qubits with photons and why photons are interesting systems with a great potential. We will then review some of the pioneering works up to what has been achieved more recently and we will conclude by what perspectives one can hope for using photonic qubits. Implicitly, in this work, we take the stand-point of a future fault-tolerant quantum computer using photons. In this review, some of the experimental technologies will be mentioned and briefly described but the reader will refer to further readings for more information onto how to produce, control and detect photonic qubits. It is also worth stating that this review has to be seen more as a first introduction to the subject.